2010
DOI: 10.1111/j.1469-7610.2010.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural activation to emotional faces in adolescents with autism spectrum disorders

Abstract: Background Autism spectrum disorders (ASD) involve a core deficit in social functioning and impairments in the ability to recognize face emotions. In an emotional faces task designed to constrain group differences in attention, the present study used functional MRI to characterize activation in the amygdala, ventral prefrontal cortex (vPFC), and striatum, three structures involved in socio-emotional processing, in adolescents with ASD. Methods Twenty-two adolescents with ASD and 20 healthy adolescents viewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 38 publications
6
84
0
5
Order By: Relevance
“…Of particular interest is the finding that the magnitude of amygdala activation to social rewards correlated with the degree of social impairments in the ASD sample, suggesting that amygdala activation during the processing of social rewards may contribute to the development or expression of autistic features. However, we note that the literature on amygdala activation to faces in autism is inconsistent: some studies have documented increased amygdala activation to faces in ASD (Dalton et al 2005a;Kleinhans et al 2009;Monk et al 2010;Weng et al 2010), whereas others have documented decreased amygdala activation to faces in ASD (Ashwin et al 2007;Critchley et al 2000;Dapretto et al 2006;Grelotti et al 2005;Hadjikhani et al 2007;Pinkham et al 2008). Thus, the implications of direct associations between amygdala activation to social rewards and clinical symptom severity are contingent on a better understanding of the nature of amygdala activation to faces in ASD.…”
Section: Responses To Monetary Rewardsmentioning
confidence: 85%
“…Of particular interest is the finding that the magnitude of amygdala activation to social rewards correlated with the degree of social impairments in the ASD sample, suggesting that amygdala activation during the processing of social rewards may contribute to the development or expression of autistic features. However, we note that the literature on amygdala activation to faces in autism is inconsistent: some studies have documented increased amygdala activation to faces in ASD (Dalton et al 2005a;Kleinhans et al 2009;Monk et al 2010;Weng et al 2010), whereas others have documented decreased amygdala activation to faces in ASD (Ashwin et al 2007;Critchley et al 2000;Dapretto et al 2006;Grelotti et al 2005;Hadjikhani et al 2007;Pinkham et al 2008). Thus, the implications of direct associations between amygdala activation to social rewards and clinical symptom severity are contingent on a better understanding of the nature of amygdala activation to faces in ASD.…”
Section: Responses To Monetary Rewardsmentioning
confidence: 85%
“…We implemented this parallel approach not to provide separate inferences about a priori hypotheses (this would represent circularity of analysis), but to illustrate different aspects of the same empirical relationship between amygdala, ASD symptoms and anxiety. While per-voxel tests better allow for localization of amygdala signals (and is by far the most widely used approach in the ASD amygdala literature-for example, see BaronCohen et al, 1999;Dalton et al, 2005;Kleinhans et al, 2009Kleinhans et al, , 2010Monk et al, 2010;Weng et al, 2011), the ROI analysis allowed for a more precise characterization of the specific anxiety symptoms contributing to variance in amygdala activation.…”
Section: Mri Data Acquisition Reduction and Analysismentioning
confidence: 99%
“…Of the four studies reporting increased rather than decreased amygdala activation in ASD (Dalton et al, 2005;Kleinhans et al, 2010;Monk et al, 2010;Weng et al, 2011), only two included measures of anxiety. Weng et al (2011) reported increased amygdala activation relative to controls, and did not find a significant relationship between amygdala activation and scores on the Spence Child Anxiety Scale. Kleinhans et al (2010), on the other hand, found a significant relationship between amygdala activation and social anxiety symptoms in ASD (measured via the Social Anxiety and Distress Scale).…”
Section: Introductionmentioning
confidence: 99%
“…Basic sensory processing could also be altered in ASD (Foss-Feig et al, 2010;Kwakye et al, 2011;Marco et al, 2011), resulting in abnormal response to almost any stimulus and without specificity for any particular task. Even with these caveats, quite a number of interesting functional neuroimaging findings have been reported that may relate to structural imaging finding, such as altered amgydala response to social stimuli (Kleinhans et al, 2009;Weng et al, 2011). The interested reader is referred to several recent reviews on this topic (Anagnostou and Taylor, 2011;Di Martino et al, 2009).…”
Section: Biomarkers In Asdmentioning
confidence: 99%